2004
DOI: 10.1007/s00455-004-0015-4
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Management of a Large Postlaryngectomy Neopharyngeal Diverticulum

Abstract: Dysphagia is common following total laryngectomy. Postlaryngectomy neopharyngeal diverticulae are known to cause postlaryngectomy dysphagia but are more frequently asymptomatic. We report a case presenting with late-onset postlaryngectomy dysphagia and a suprastomal swelling secondary to such a diverticulum. The patient was managed conservatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
(12 reference statements)
1
4
0
Order By: Relevance
“…This would then cause gradual herniation over time of the pharyngeal mucosa proximal to the stricture, and the pseudo‐diverticulum and pseudo‐epiglottis would become more apparent. Our high percentage of pseudo‐epiglottis formation is in accordance with the available literature, with an incidence varying from 35% to 86% 3,6,16–18 . It has been suggested that the pseudo‐epiglottis is more likely to occur following vertical closure of the neopharynx 2,5,19 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This would then cause gradual herniation over time of the pharyngeal mucosa proximal to the stricture, and the pseudo‐diverticulum and pseudo‐epiglottis would become more apparent. Our high percentage of pseudo‐epiglottis formation is in accordance with the available literature, with an incidence varying from 35% to 86% 3,6,16–18 . It has been suggested that the pseudo‐epiglottis is more likely to occur following vertical closure of the neopharynx 2,5,19 .…”
Section: Discussionsupporting
confidence: 90%
“…Our high percentage of pseudo-epiglottis formation is in accordance with the available literature, with an incidence varying from 35% to 86%. 3,6,[16][17][18] It has been suggested that the pseudo-epiglottis is more likely to occur following vertical closure of the neopharynx. 2,5,19 One of the studies reported pseudo-epiglottis formation in 85% of patients after vertical closure, compared to only 18% following a T-shape repair.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of postoperative dysphagia varies from 17 to 72% [1, 5, 6]. This symptom has several causes, such as tumour recurrence, pharyngeal dysmotility, stricture formation, pharyngocutaneous fistulas, and postoperative radiotherapy but also the formation of a pseudo-diverticulum [79]. The pseudo-diverticulum is an anteriorly located mucosalized pouch of the neopharyngeal lumen, situated at the base of the tongue (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…According to relevant literature the incidence ranges from 35 to 86% [79, 13, 14]. Although the possible association between closure technique in laryngectomy, pseudo-diverticulum and postoperative dysphagia has been described before, little scientific research has been published on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Following total laryngectomy and free-flap reconstruction, muscle contraction is limited at the suture lines within the operative site, reducing peristalsis during swallowing and often causing dysphagia [ 2 ]. Poor coordination of the remaining pharyngeal constrictor muscles can also contribute to dysphagia [ 3 ].…”
Section: Discussionmentioning
confidence: 99%